Medical radiation exposures for diagnostic radiology in Malaysia - Ng, K.H.; Abdullah, B.J.J.; Sivalingam, S. (1999)
The medical radiation usage for diagnostic radiology in Malaysia (a Level II country) for 1990-1994 is reported, enabling a comparison to be made for the first time with the United Nations Scientific Committee on the Effects of Atomic Radiation Report. In 1994, the number of physicians, radiologists, x-ray units, and x-ray examinations per 1,000 population was 0.45, 0.005, 0.065, and 183, respectively. (Level I countries had averages of 2.6, 0.072, 0.35, and 860, respectively). In 1994, a total of 3.6 million x-ray examinations were performed; the annual effective dose per capita to the population was 0.05 mSv, and the collective effective dose aas 1,000 person-Sv. Chest examinations contributed 63 of the total. Almost all examinations experienced increasing frequency from 1990 to 1994 except for barium studies, cholecystography, and intravenous urography (-23, -36, -51). These decreases are related to the increasing use of ultrasound and greater availability of fiberoptic endoscopy. Notable increases during the same period were observed in computed tomography (161), cardiac procedures (190), and mammography (240). In order to progress from Level II to Level I status Malaysia needs to expand and upgrade radiological service in tandem with the health care development of the country.